Central arch mandibular reconstruction after surgery of oral carcinoma: an observational experience at MDACC, Houston, Texas, USA - Das, Prafulla Kumar; Robb, Geoffrey L. (International Journal of Research in Medical Sciences, 2017)
Background: Reconstruction of head and neck defects in general and oro-mandibular defects in particular, represents a challenge to the head and neck reconstructive surgeon. The most common indication of oro-mandibular reconstruction remains ablative surgery for neoplastic disease of the oral cavity and oropharynx. The principal purpose was evaluation of the various methods of such reconstruction done in order to achieve the best cosmetic and functional outcome in terms of adequate mouth opening, oral competence, deglutition of semisolid to solid foods, speech intelligibility, minimum donor site morbidity and complication. Methods: The authors presented an observational work on the reconstruction of head and neck cancer after their curative excision, mostly oro-mandibular defects of various sizes ranging from 6cm to 12cm with special reference to the central arch during the first authors fellowship to MD Anderson Cancer Center (MDACC), Texas, where the second author was the supervisor. Results: The authors reported 24 reconstructions including 10 bony reconstructions. The free flap was preferred to pedicle flap for the reason of better aesthetic and functional outcome. The free fibula was mostly preferred due to its characters akin to the native mandible. Seventy-five patients were also observed in the outpatient clinic and evaluated during the follow up period for aesthetic and functional aspects, donor site morbidity, and long term complications. The first auther also evaluated that the incidence of primary closure with residual cosmetic defect in his study had come down from 28.47% before MDACC visit to only 4.38% today owing to more number of free and pedicle flaps were used. Conclusions: The free fibula was found to be the best option for mandible reconstruction overall. Observation within high volume centers however limited it may be, certainly upgraded the knowledge and working skills of the second author after he came back to his institution of Acharya Harihar Regional Cancer Center (AHRCC) in India.